New signal readout method for ultrahigh-sensitivity CMOS image sensor. - Watabe, T. (IEEE Transactions on electron devices)
We propose a new signal readout method that uses a charge-transfer circuit. Its application is to an ultrahigh-sensitivity CMOS image sensor on which an avalanche-mode photoconductive film is overlaid. The charge-transfer circuit makes it possible to obtain high signal-to-noise ratio features by transferring signal charges accumulated in each photodiode to a parasitic capacitance that is small compared with the photodiode capacitance. A 138 × 138 passive-pixel prototype sensor that had the charge-transfer circuit in each column was fabricated and tested. The prototype's column-to-column fixed-pattern noise and random noise were, respectively, 56.7 and 58.4 dB below the saturation signal level, which demonstrated its potential as a signal readout circuit for a next-generation ultrahigh-sensitivity CMOS image sensor.